IN VITRO HYPOGLYCAEMIC EVALUATION OF SEVEN CULINARY PLANTS OF NORTH EAST INDIA AGAINST TYPE 2 DIABETES - Dutta, Jayashree; Mc, Kalita (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The goal of the present study is to provide an in vitro evidence for potential inhibition of the α-amylase and α-glucosidase enzyme by seven culinary plants of North east India followed by their phytochemical screening. Methods: The different parts (leaves, seeds, bark, and fruit) of the selected plants were chosen for the study. Collected plant parts were a shade dried, powdered, and successively extracted using petroleum ether, acetone, and methanol. The obtained extracts were quantitatively assayed for in vitro α-amylase and α-glucosidase enzyme inhibitory activity. The collected plant materials were screened qualitatively for detection of several bioactive compounds. Results: In our study, we found that among all the screened culinary plants the highest α-amylase inhibitory activity was demonstrated by Dillenia indica Linn. fruit methanol extract with a minimum IC value of 02.45 ± 0.305 mg/ml, and the highest α-glucosidase inhibitory activity was demonstrated by D. indica leaves methanol extract with a very minimal IC 50 value of 01.78 ± 0.331 mg/ml compared to the standard drug acarbose IC 50 - 05.43 ± 0.280 mg/ml for α-amylase and IC 50 - 50 03.06 ± 0.072 mg/ml for α-glucosidase, respectively. Phytochemical screening reveals the presence of several bioactive groups such as carbohydrate, protein, saponin, tannin, flavonoid, alkaloid, and terpenoids in all studied plants. Conclusion: The study concludes that selected culinary plants of North East India are capable of inhibiting carbohydrate metabolizing enzyme α-amylase and α-glucosidase, and the presence of bioactive compounds in these plants add on the potentiality of these plants to reduce the postprandial hyperglycemia. Keywords: Diabetes mellitus, Post-prandial hyperglycemia, α-amylase, α-glucosidase, Culinary plants.